Basal Joint Arthroplasty Decreases Carpal Tunnel Pressure. (September 2015) - Lutsky, Kevin; Ilyas, Asif; Kim, Nayoung; Beredjiklian, Pedro
Background: There is a well-documented association between carpal tunnel syndrome (CTS) and thumb carpometacarpal (CMC) arthritis, and these conditions commonly coexist. We have observed that patients who have previously undergone thumb basal joint arthroplasty (BJA) seem rarely to present subsequently with CTS. Our hypothesis is that BJA decreases the pressure within the carpal tunnel. Methods: Twenty-eight patients (6 with coexistent CTS) undergoing BJA were enrolled in the study. The pressure within the carpal tunnel immediately before and after BJA was measured using a commercially available pressure monitor device (Stryker STIC; Kalamazoo, MI). In patients with concomitant CTS undergoing both BJA and carpal tunnel release (CTR), the pressure was measured after BJA but prior to release of the transverse carpal ligament. Results: The pressure within the carpal tunnel decreased after BJA in all patients. There were 3 patients with stage II arthritis, 15 patients with stage III arthritis, and 10 patients with stage IV arthritis. The mean pressure prior to BJA among all patients was 23.9 mmHg and decreased to 11.0 mmHg after BJA. Patients with concomitant CTS had a mean pre-BJA pressure of 26.5 mmHg, which decreased to 7.3 mmHg after BJA. Conclusions: BJA decompresses the carpal tunnel and decreases the pressure within. In patients with concomitant CTS, the BJA alone (without additional release of the transverse carpal ligament) decreases the carpal tunnel pressure. Further study is warranted to determine the need for discrete release of the transverse carpal ligament in patients with CTS who are undergoing BJA. Level of Evidence: Level II, diagnostic.